If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3k + -8 = -2 Reorder the terms: -8 + -3k = -2 Solving -8 + -3k = -2 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -3k = -2 + 8 Combine like terms: -8 + 8 = 0 0 + -3k = -2 + 8 -3k = -2 + 8 Combine like terms: -2 + 8 = 6 -3k = 6 Divide each side by '-3'. k = -2 Simplifying k = -2
| 6n+5=-85-9n | | 2x^2-15-20=0 | | 3x+9=9x+99 | | 4(y-1)=y+13 | | 420/36=f/30 | | 4y+1=y+13 | | -56-3v=7-10v | | 2x-10=2x+10+1 | | 4x-113=4x+9 | | 3c+5c-5c= | | 3x+28=9x-8 | | 11(p-3)=2y+2 | | 5x-2=4x+11 | | 0.3(2x-3)=0.7(8-x) | | 5c+7=95-6c | | 5x-69=7x+21 | | 1/2x-9=x-3 | | .25x-y=3 | | 2x+10=5x-80 | | 12x-25=8x+23 | | -5x/2=-1 | | 4x-5y=-32 | | 10x+20x=150 | | 4x-5y=-32graph | | 3x/2=-3 | | 8x+5-4x=-20 | | x-1=x^2-6x+9 | | -1x/3=-12 | | 4t+16-6= | | x/5+7=27 | | 5x^2-40x-10=0 | | 1x/3=0 |